2013
DOI: 10.1177/0309364612471369
|View full text |Cite
|
Sign up to set email alerts
|

Orthotic variations in the management of infantile tibia vara and the results of treatment

Abstract: Background: Infantile tibia vara is an acquired form of tibial deformity associated with tibial varus and internal torsion. Several methods have been described for orthotics treatment. The purpose of this study was to determine the effectiveness of orthotics treatment in infantile tibia vara. Study design: Controlled trial. Objective: The aim of this study was to compare the effect of different types of orthoses and correction methods on decreasing the curve in children with severe genu varum. Methods: Three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Radiographs are necessary for diagnosis. 5,6 The studies have identified a linear correlation between infantile Blount disease and body mass index (BMI). There has been an increase in the incidence of this disease, which in parallel to the rise of obesity rates in children.…”
Section: Ilustrasi Kasusmentioning
confidence: 99%
“…Radiographs are necessary for diagnosis. 5,6 The studies have identified a linear correlation between infantile Blount disease and body mass index (BMI). There has been an increase in the incidence of this disease, which in parallel to the rise of obesity rates in children.…”
Section: Ilustrasi Kasusmentioning
confidence: 99%
“…Nonsurgical treatment of ITV has been somewhat controversial. However, recent studies have reported success when knee-ankle-foot orthosis (KAFO) was used nearly full-time to improve biomechanics in patients under 4 years of age [ 14 16 ]. The effectiveness of orthoses with corrective forces and/or distraction systems is related to their ability to relieve weight bearing stresses on the medial physeal region of the proximal tibia.…”
Section: Introductionmentioning
confidence: 99%
“…The sole of the foot usually lies flat on the ground during the stance phase, despite varus deformity due to concomitant talocrural joint deformity combined with medial rotation of the leg bones 10 .The nonsurgical treatment of ITV has been controversial. However, recent studies have indicated success when a knee ankle foot orthosis (KAFO) was used nearly full-time to improve biomechanics in patients aged <4 years [11][12][13] . The efficacy of orthoses with corrective forces and/or distraction systems is related to their ability in relieving weight-bearing stresses on the medial physeal region of the proximal tibia.Alsancak et al reported that a single upright KAFO with a drop lock knee joint was effective for the treatment of ITV in 20 children aged up to 38 months 11 .…”
mentioning
confidence: 99%
“…The nonsurgical treatment of ITV has been controversial. However, recent studies have indicated success when a knee ankle foot orthosis (KAFO) was used nearly full-time to improve biomechanics in patients aged <4 years [11][12][13] . The efficacy of orthoses with corrective forces and/or distraction systems is related to their ability in relieving weight-bearing stresses on the medial physeal region of the proximal tibia.…”
mentioning
confidence: 99%
See 1 more Smart Citation